2022
DOI: 10.1128/mbio.02717-21
|View full text |Cite
|
Sign up to set email alerts
|

Acyl-Coenzyme A Synthetase Long-Chain Family Member 4 Is Involved in Viral Replication Organelle Formation and Facilitates Virus Replication via Ferroptosis

Abstract: We provide the first evidence for the role of ACSL4 in enterovirus replication organelle formation. Moreover, both enteroviruses and coronaviruses induce ferroptosis via ACSL4. These findings establish a novel regulatory mechanism for viral replication. The inhibition of ACSL4 by ferroptosis inhibitors can reduce viral yields of enteroviruses and coronaviruses, including SARS-CoV-2, implying that ACSL4-mediated ferroptosis is a promising therapeutic target for viral diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 45 publications
1
41
0
Order By: Relevance
“…Those authors used several inhibitors targeting the cell cycle and the endocytosis pathway and showed that both are critical for coronavirus infection. Kung et al ( 170 ) found that ACSL4-mediated ferroptosis is required for HCoV-229E infection. They identified host factors using CRISPR loss-of-function screening with coxsackievirus A6.…”
Section: High-throughput Screening Identification Of Host Cell Factor...mentioning
confidence: 99%
“…Those authors used several inhibitors targeting the cell cycle and the endocytosis pathway and showed that both are critical for coronavirus infection. Kung et al ( 170 ) found that ACSL4-mediated ferroptosis is required for HCoV-229E infection. They identified host factors using CRISPR loss-of-function screening with coxsackievirus A6.…”
Section: High-throughput Screening Identification Of Host Cell Factor...mentioning
confidence: 99%
“…( Yao Y. et al, 2021 ). (B) During SARs-Cov-2 infection, the Gpx4 mRNA level was decreased ( Wang et al, 2021a ) and iron overload was observed ( Zhou C. et al, 2020 ), and the induction of ferroptosis by SARS-Cov-2 could be rescued by ASCL4 inhibitors ( Kung et al, 2022 )…”
Section: Mechanism Of Ferroptosismentioning
confidence: 99%
“…What’s more, lipid metabolism is involved in viral replication by regulation of the formation, assembly, and release of replicative organelles. ASCL4, a key factor involved in lipid metabolism and ferroptosis, greatly promoted the replication of some enteroviruses and coronaviruses ( Kung et al, 2022 ). In ASCL4 knockout cells, the viral titers of enteroviruses such as CV-A6, coronaviruses such as Cov-229E, influenza virus (IAV), and Zika virus were lower than those in the normal cells.…”
Section: Mechanism Of Ferroptosismentioning
confidence: 99%
See 1 more Smart Citation
“…Enteroviruses can induce ferroptosis through ACSL4. However, its inhibitors can reduce enteroviral yields ( 81 ).…”
Section: Viral Myocarditis and Ferroptosismentioning
confidence: 99%